Training Executive Functions to Improve Academic Achievement: Tackling Avenues to Far Transfer - Gunzenhauser, Catherine; Nückles, Matthias (Frontiers in Psychology, 2021)
The aim of training executive functioning (EF) is usually to improve the ability to attain real-life goals such as academic achievement, that is, far transfer. Although many EF trainings are successful in improving EF, far transfer is more difficult to achieve (cf. Diamond & Lee, 2011; Sala & Gobet, 2020). In this perspective article, we focus on the transfer of EF training to academic performance. First, we disentangle possible sources of transfer problems. We argue that EF can facilitate academic performance via two specific pathways, namely learning-related behavior and learning-related cognition, and we discuss how domain-specific factors (e.g., task-specific demands and prior knowledge) may influence the successful application of EF to learning in this domain. Second, we discuss how the school setting can be used to enhance EF training with approaches to facilitating far transfer to academic achievement. Specifically, we suggest that training EF as a means to improve academic performance is most promising in young students, for whom both behavioral and domain-specific cognitive demands of formal schooling are quite novel challenges. Furthermore, we outline that students could be supported in far transfer of trained EF by being informed of the specific relevance of these skills for learning-related behaviors and by having them practice EF under such authentic conditions. Moreover, we suggest that in order to promote ongoing effects of EF training beyond short-term interventions, teachers should be enabled to consider the specific EF components that might facilitate and support students’ acquisition of a particular subject matter.